An infinite stiffness aerostatic pad with a diaphragm valve. (January 2020) - Ghodsiyeh, Danial; Colombo, Federico; Lentini, Luigi; Raparelli, Terenziano; Trivella, Andrea; Viktorov, Vladimir
Abstract: This work presents a prototype of a compensated aerostatic pad which consists in the integration of a commercial pad with a custom-built regulating pneumatic valve. The performance of the system is studied both in static and transient conditions. The stability and the capacity of compensation of the protype are proved performing step force tests. Moreover, the paper describes the lumped parameter model of the compensated pad. To take into account the compensating action of the valve, a distinctive numerical procedure was developed. Experimental and numerical results are in good agreement and demonstrate that once a suitable initial set-up is defined, the integrated regulating valve allows bearings with quasi-static infinite stiffness to be obtained. Highlights: The paper proposes a compensation method to obtain air pads with quasi-static infinite stiffness. This low-cost solution makes it possible to increase the bearing performance and it can be used with commercial air pads of different sizes. The mechanical structure and the functioning of the valve are described along with the proposed compensation method. The performance of the system is investigated numerically and experimentally. The paper describes a lumped parameter model of the system which was developed through a specific iterative procedure to take into account the regulating action of the valve. The proposed model is a valuable tool to design and study this kind of compensated bearings. Numerical and experimental results demonstrate the good accuracy of the model and the effectiveness of the proposed solution.